Historical Reference to Ice Islands - Loewe, F. (ARCTIC, 1971)
Some years ago M. Dunbar gave a detailed account of earlier ice reports which could refer to ice islands, as distinguished by G. Hattersley-Smith from other ice in the polar sea by their great unit area, thickness, structural strength and rolling relief. Among the old descriptions of 'floebergs' and 'palaeocrystic ice' some of Greely's come closest to a description of an ice island. Another early report might be worth mentioning: Franz Boas, the German-born anthropologist and later professor at Columbia University states that in October 1883 a huge iceberg drifted into Cumberland Sound, Baffin Island. It had a height of 15 m to 20 m, a length of 14 km and a width of 5 km. The total thickness of 100 m to 150 m could be seen when the ice broke into pieces. The estimated volume was 13 cu km. Similar ice formations of smaller size had been repeatedly encountered when approaching Cumberland Sound. The upper surface consisted of long low rounded parallel rolls with a wavelength of about 150 m and extending over 1 km to 3 km. The surface and the uppermost 2 m of the ice contained stones; no stratification or crevasses were visible. The description fits that of a typical ice island. That ice islands from the northern coast of Ellesmere Island can reach Baffin Bay and Cumberland Sound is shown by the recent drift of ice island WH55; a segment of at least 14 sq km passed through southern Davis Strait.